4sinx cosx-6 sinx+2cosx=3

0 голосов
110 просмотров

4sinx cosx-6 sinx+2cosx=3


Алгебра (724 баллов) | 110 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

4sinx*cosx-6sinx+2cosx=3
4sinx*cosx+2cosx-6sinx-3=0
2cosx*(2sinx+1)-3*(2sinx+1)=0
(2sinx+1)*(2cosx-3)=0
2sinx+1=0  или  2cosx-3=0

1. 2sinx+1=0
2sinx=-1
sinx=-1/2
x=(-1) ^{n}*arcsin(- \frac{1}{2} )+ \pi n, n∈Z
x=(-1) ^{n+1}*arcsin \frac{1}{2}+ \pi n, n∈Z
x=(-1) ^{n+1}* \frac{ \pi }{6}+ \pi n, n∈Z

2. 2cosx-3=0
2cosx=3
cosx=1,5.  1,5∉[-1;1] решений нет

ответ: x=(-1) ^{n+1}* \frac{ \pi }{6}+ \pi n, n∈Z

(276k баллов)